2016
DOI: 10.1038/srep27838
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral outer membrane protein LipL32 induces inflammation and kidney injury in zebrafish larvae

Abstract: Leptospirosis is an often overlooked cause of acute kidney injury that can lead to multiple organ failure and even death. The principle protein that conserved in many pathogenic leptospires is the outer membrane protein LipL32. However, the role of LipL32 in the pathogenesis of renal injury in leptospirosis is not entirely clear. Here we studied the effects of LipL32 on the developing kidney in zebrafish larvae. Incubation of zebrafish larvae with Leptospira santarosai serovar Shermani induced acute tubular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 57 publications
(83 reference statements)
0
29
0
Order By: Relevance
“…plays an important role in the establishment of the AKI that is observed in Weil’s syndrome. In contrast, LipL32 protein did not produce a decrease in the GFR, despite a report that LipL32 induced interstitial nephritis-mediated gene expression in cultured mouse proximal tubule cells [34] and acute tubular injury in proximal pronephric ducts from zebrafish larvae kidneys [35]. These experiments were performed using in vitro preparations and another animal species.…”
Section: Discussionmentioning
confidence: 99%
“…plays an important role in the establishment of the AKI that is observed in Weil’s syndrome. In contrast, LipL32 protein did not produce a decrease in the GFR, despite a report that LipL32 induced interstitial nephritis-mediated gene expression in cultured mouse proximal tubule cells [34] and acute tubular injury in proximal pronephric ducts from zebrafish larvae kidneys [35]. These experiments were performed using in vitro preparations and another animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data showed the presence of Leptospira DNA in the urine of some of the patients [13], and uDA1 was also positive in kidney derived-DNA-positive cases (unpublished observation), further supporting that neutrophil activation is caused by bacteria. Very recently, it was shown that the leptospiral outer membrane protein LipL32 induces inflammation, including leukocyte infiltration and kidney injury, in zebrafish larvae [36]. Therefore, therapies against neutrophil-derived inflammation would be recommended in uDA1-positive leptospirosis, and in fact azithromycin, which is known to inhibit neutrophil activation and also to have antibacterial activity [11], was demonstrated to be effective against this disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…Leptospira outer membrane protein may also induce activation of the transforming growth factor-beta/Smad-associated fibrosis pathway leading to accumulation of extracellular matrix [24]. Leptospirosis renal disease, therefore, is a model for understanding the result of pathogen-induced tubulointerstitial nephritis and fibrosis [25][26][27]. In particular, toll-like receptors may be important mediators.…”
Section: Leptospirosis Renal Diseasementioning
confidence: 99%